Design of AES Pipelined Architecture for Image Encryption/Decryption Module - Pravin V. Kinge; S.J. Honale; C.M. Bobade (Institute of Advanced Engineering and Science, 2014)
The relentless growth of Internet and communication technologies has made the extensive use of images unavoidable. The specific characteristics of image like high transmission rate with limited bandwidth, redundancy, bulk capacity and correlation among pixels makes standard algorithms not suitable for image encryption. In order to overcome these limitations for real time applications, design of new algorithms that require less computational power while preserving a sufficient level of security has always been a subject of interest. Here Advanced Encryption Standard (AES),as the most widely used encryption algorithm in many security applications. AES standard has different key size variants, where longer bit keys provide more secure ciphered text output. The available AES algorithm is used for data and it is also suitable for image encryption and decryption to protect the confidential image from an unauthorized access. This project proposes a method in which the image data is an input to Pipelined AES algorithm through Textio, to obtain the encrypted image. and the encrypted image is the input to Pipelined AES Decryption to get the original image. This project proposed to implement the 128,192 & 256 bit Pipelined AES algorithm for image encryption and decryption, also to compare the latency , efficiency, security, frequency & throughput . The proposed work will be synthesized and simulated on FPGA family of Xilink ISE 13.2 and Modelsim tool respectively in Very high speed integrated circuit Hardware Description Language.